Meningkatkan Pemahaman Warna dan Angka pada Anak ADHD melalui Metode Pembelajaran Interaktif di TK Keledang Samarinda - Susanti, Devi Triana; Amalia, Ratih; Amara, Salsabilla; Nurhidayah, Nurhidayah; Safrah, Safrah; Sinar, Sinar; Sari, Erna (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Children with Attention Deficit Hyperactivity Disorder (ADHD) often encounter difficulties in grasping basic concepts such as colors and numbers, which are crucial for their cognitive development. This study aims to enhance the understanding of colors and numbers in ADHD children through interactive learning methods at TK Keledang Samarinda. The research utilized a Classroom Action Research (CAR) design over two cycles, involving two ADHD children aged 6 and 7. Data were collected using observations, image-based tests, interviews, and documentation, followed by qualitative and quantitative analyses. The results revealed a substantial improvement in color and number comprehension, increasing from 41.6% in the pre-cycle to 87.5% in the second cycle. Interactive learning methods employing visual and manipulative media, such as colored number cards and color-matching games, effectively boosted the children’s focus, active participation, and learning motivation. However, challenges such as inconsistent reinforcement between home and school practices and limited variation in learning media were identified. This study demonstrates that hands-on, interactive learning approaches effectively support the cognitive development of ADHD children. The findings highlight the importance of engaging, experience-based methods tailored to individual needs. Recommendations for future research include developing more innovative learning media and fostering greater parental involvement to ensure consistency in learning practices across environments. Further studies involving larger samples are recommended to validate these findings and explore broader applications in early childhood education.